The dynamics of private property: between individual rights and common interests - Yelanska, Svitlana (Riga Graduate School of Law, 2021)
The present research explores the tension implicit in the right to property as an exclusionary right. The conceptualization of the right to property as a necessary component of individual freedom stands at odds with a universal exercise of the right in the context of scarcity. Both moral and economic considerations align in the necessity for property, but these justifications are of a principally divergent order. The natural law perspective is predominantly anchored in the atomic – the interest of the individual in personal freedom and well-being. The focal point of the economics approach is in the aggregate – the benefit to be reaped in the rights’ systematic application. The present work explores the interaction between the two -whether a focus on the aggregate is capable of undermining the atomic, manifested in the potential for inequality. It is concluded that tension between the two is endemic to the right to property, but can be alleviated through appropriate legal safeguards which prioritize welfare and constrain accumulation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Property and real estate law; Natural law